The Challenges and Future of Marine Debris Policy in Indonesia and Taiwan Case Studies - Imelda Masni Juniaty Sianipar; I Wayan Koko Suryawan; Sun Rise Tarigan (Journal of Sustainable Infrastructure, 2022)
There is evidence that marine plastic pollution affects marine life and ecological services. The potential hazard to human health from chemical additions in plastics is also present. Although desirable, the recycling of plastics is now limited by the complexity of the materials and chemicals, the limitations of available technologies, and market demands. This study was conducted to discover the challenges and future of marine debris policy. This study takes two locations, Indonesia and Taiwan, which have issued marine debris policies simultaneously. At the same time, the Indonesian and Taiwanese governments 2018 issued a policy to reduce marine debris. Following Presidential Decree Number 83/2018 concerning Handling Marine Debris, the Government of Indonesia published a National Action Plan for Handling Marine Debris for 2018–2025. Following this law, the Indonesian government agreed to handle 70% of the solid trash generated within eight years between 2018 and 2025, eliminate marine debris by 70%, and reduce solid waste by 30%. In Taiwan, the "Action Plan of Marine Debris Governance, " issued in 2018 by this alliance and the EPA, contains a schedule for the phase-out of four single-use plastic items (plastic bags, straws, utensils, and takeaway cups). Source reduction, prevention and removal, monitoring and surveying (including research), and outreach and public involvement are the four objectives of this action plan. Although implementing the policy is different, the objectives carried out in Indonesia and Taiwan are the same: reducing waste from sources and increasing community participation in action plan programs.